Ocean acidification mediates photosynthetic response to UV radiation and temperature increase in the diatom Phaeodactylum tricornutum ... : يتوسط تحمض المحيطات استجابة التمثيل الضوئي للأشعة فوق البنفسجية وزيادة درجة الحرارة فيالدياتوم Phaeodactylum tricornutum </ i> ... - Y. Li; Kunshan Gao; Virginia E. Villafañe; E. Walter Helbling (OpenAlex, 2012)
Abstract. Increasing atmospheric CO2 concentration is responsible for progressive ocean acidification, ocean warming as well as decreased thickness of upper mixing layer (UML), thus exposing phytoplankton cells not only to lower pH and higher temperatures but also to higher levels of solar UV radiation. In order to evaluate the combined effects of ocean acidification, UV radiation and temperature, we used the diatom Phaeodactylum tricornutum as a model organism and examined its physiological performance after grown under two CO2 concentrations (390 and 1000 µatm) for more than 20 generations. Compared to the ambient CO2 level (390 µatm), growth at the elevated CO2 concentration increased non-photochemical quenching (NPQ) of cells and partially counteracted the harm to PSII caused by UV-A and UV-B. Such an effect was less pronounced under increased temperature levels. As for photosynthetic carbon fixation, the rate increased with increasing temperature from 15 to 25 °C, regardless of their growth CO2 levels. ... : الملخص. زيادة تركيز ثاني أكسيد الكربون في الغلاف الجوي مسؤولة عن تحمض المحيطات التدريجي، وارتفاع درجة حرارة المحيطات وكذلك انخفاض سمك طبقة الخلط العليا (UML)، وبالتالي تعريض خلايا العوالق النباتية ليس فقط لخفض درجة الحموضة وارتفاع درجات الحرارة ولكن أيضًا لمستويات أعلى من الأشعة فوق البنفسجية الشمسية. من أجل تقييم الآثار المجتمعة لتحمض المحيطات والأشعة فوق البنفسجية ودرجة الحرارة، استخدمنا المشطورة Phaeodactylum tricornutum ككائن نموذجي وفحصنا أدائها الفسيولوجي بعد نموها تحت تركيزين من ثاني أكسيد الكربون (390 و 1000 ميكرومتر) لأكثر من 20 جيلًا. بالمقارنة مع مستوى ثاني أكسيد الكربون المحيط (390 ميكرومتر)، أدى النمو عند تركيز ثاني أكسيد الكربون المرتفع إلى زيادة التبريد غير الكيميائي للخلايا (NPQ) وعكس جزئيًا الضرر الذي يلحق بـ PSII الناجم عن الأشعة فوق البنفسجية A و UV - B. كان هذا التأثير أقل وضوحًا في ظل زيادة مستويات درجة الحرارة. أما بالنسبة لتثبيت الكربون الضوئي، فقد زاد المعدل مع زيادة درجة الحرارة من 15 إلى 25 درجة مئوية، بغض النظر عن نمو مستويات ثاني أكسيد الكربون. بالإضافة إلى ذلك، كان تثبيط التمثيل ...